Immunohistochemical localisation and effect of matrix metalloproteinases and their inhibitors on canine spontaneous periodontitis. (22nd August 2015) - Kaiser, S. M.; Thiel, C.; Kramer, M.; Raddatz, B. B.; Failing, K.; Alldinger, S.
Abstract : Periodontitis is commonly observed in dogs. In human medicine, it is well documented that matrix metalloproteinases (MMPs) are involved in the destruction of the periodontium. Therefore, the aim of this prospective study was to investigate the impact of MMPs and their inhibitors, the TIMPs (tissue inhibitors of metalloproteinases), on canine periodontitis. The oral cavities of 57 dogs were examined clinically and radiologically. Gingival biopsies were obtained from the examined dogs and histologically analysed via haematoxylin and eosin stained sections. Immunohistological detection of MMP‐2, MMP‐3, MMP‐8 and MMP‐9 as well as TIMP‐1 and TIMP‐2 was performed by the avidin‐biotin peroxidase complex technique. All sections were evaluated by light microscopy. Statistically significant positive correlations were detected between the histologically verified degree of inflammation and the expression of MMP‐2, MMP‐3, MMP‐8 and MMP‐9 as well as between changes in collagen fibre content and the occurrence of MMP‐2, MMP‐8 and MMP‐9. Concerning TIMP‐1 and TIMP‐2, non‐significant, generally negative correlations were observed. In summary, in canine periodontitis, an increased expression of the above mentioned MMPs and a tendentially decreased expression of TIMPs are present. In conclusion, in canine periodontitis, a MMP‐TIMP imbalance is suggestive of contributing to the destruction of the periodontium.